Penerapan Video Animasi Berbasis Ms. Power Point Bagi Siswa Madrasah Aliyah di Kabupaten Gowa : id - A. Ramli Rasyid; Baso Riadi Husda; Ady Rukma; Hamzah Nur; Sudarmanto Jayanegara (Program Studi Sarjana Terapan PTM FT UNM, 2024)
The targets this training are (1) Students are able to change their mindset and easily understand all material explanations and practices demonstrated. (2) To understand simple techniques for making animated video media designs which are trained to MTS/MA Muhammadiyah Cambajawaya District students. Gowa via the Ms. Office Power Point. (3) To create interesting and interactive animated video designs through the Ms. Office Power Point. (4) There is a change in students' knowledge and thinking patterns with the application of different learning media. (5) Students are motivated to learn through the application of animated video learning media through the Ms. application. Office Power Point. (6) To interested in following subjects taught with new learning media designs based on animated videos. The approach method used is carrying out the implementation of Ms. Office Power Point for Mts/Ma Mahammadiyah Teachers in Kab. Gowa. To be more focused, the approach methods used are lecture, question and answer, discussion and demonstration. The output produced in the training on creating and implementing animated video learning media using the Ms. application. Microsoft Office Power Point is a learning media design product and increases the knowledge of MTS/MA Muhammadiyah Cambajawaya students through mentoring so that students' mindsets become more modern. With this training it is hoped that it can improve abilities, interests and learning outcomes students in applying animated video learning media.